2008
DOI: 10.23869/bphjbr.13.2.20087
|View full text |Cite
|
Sign up to set email alerts
|

HUBUNGAN KEKERABATAN BURUNG GELATIK JAWA (Padda oryzivora) DI PULAU JAWA BERDASARKAN KARAKTER MORFOLOGI

Abstract: The study was conducted to evaluated the phylogenetics of the morphology character of gelatik jawa (Padda oryzivora). Fifty four P. oryzivora from natural population in Surabaya, Malang, Ngawi, Bekasi, Karawang, Cirebon, Bogor, Semarang, Magelang, Yogyakarta and Prambanan is adapted to condition of the research for 2 week. After individual identification card with bird ring and measured of the quantitative and qualitative of morphology characters, morphology characters of the bird were analysed of the phylogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0
4

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
0
1
0
4
Order By: Relevance
“…Masa inkubasi jamur dari kedua metode tersebut adalah masingmasing tiga hari. Seperti yang dilakukan oleh Suciatmih (2006a), pengenceran 10 -3 digunakan untuk mengisolasi jamur yang diinkubasi pada suhu ruang, sedangkan isolasi jamur untuk perlakuan inkubasi pada suhu 45 o C menggunakan pengenceran 10 -1 . Masing-masing sampel tanah yang diuji diulang dua kali.…”
Section: Isolasi Jamurunclassified
See 3 more Smart Citations
“…Masa inkubasi jamur dari kedua metode tersebut adalah masingmasing tiga hari. Seperti yang dilakukan oleh Suciatmih (2006a), pengenceran 10 -3 digunakan untuk mengisolasi jamur yang diinkubasi pada suhu ruang, sedangkan isolasi jamur untuk perlakuan inkubasi pada suhu 45 o C menggunakan pengenceran 10 -1 . Masing-masing sampel tanah yang diuji diulang dua kali.…”
Section: Isolasi Jamurunclassified
“…Jamur memerlukan partikel humus dan lebih menyukai keadaan yang lebih asam untuk pertumbuhannya. Pada Tabel yang sama diketahui pula bahwa populasi jamur baik dari tanaman pisang maupun ubi kayu yang ditanam baik di lahan gambut maupun tanah aluvial yang diinkubasi pada suhu ruang lebih besar daripada suhu 45 o C. Hasil yang sama dilaporkan pula oleh Suciatmih (2006a) pada tanah bekas terbakar di Wanariset, Kalimantan Timur.…”
Section: Hasil Dan Pembahasanunclassified
See 2 more Smart Citations
“…Neary et al (1999) reported that in burned soil, the nitrogen content is lower than that of in the unburned soils, while calcium content is higher on burnt soil, and potassium, magnesium and phosphorus contents remain unchanged. Forest fires can cause loss of biodiversity and alter soil chemical and physical wealth, so they will affect the composition of soil microbes (Suciatmih, 2008).…”
Section: Introductionmentioning
confidence: 99%